Carbon quantum dots (CQDs)/Ce doped NiO nanocomposite for high performance supercapacitor. (June 2021) - Al-Enizi, Abdullah M.; Ubaidullah, Mohd; Kumar, Dinesh
Highlights: Fabrication of novel carbon quantum dots/Ce-doped nickel oxide (CQDs/Ce-NiO) nanocomposite. High BET surface area of ∼731 m 2 g −1 and mesopores of ∼17 nm estimated. High specific capacitance 2487 F g −1 by CV at 5 mV s −1 and 2513 F g −1 by CGD 0.5 A g −1 . The CGD stability showed ∼97 % capacitance retention after 2000 segments. Abstract: A cost effective novel carbon quantum dots/Ce-doped nickel oxide (CQDs/Ce-NiO) nanocomposite was synthesized via hydrothermal route. An exceptional BET surface area of 731 m 2 g −1 and mesoporosity (∼17 nm) was estimated. In three-electrode system an excellent electrochemical behaviour was demonstrated by CQDs/Ce-NiO nanocomposite with high specific capacitance of ∼2487 F g -1 by cyclic voltammograms at a scan rate of 5 mV s -1 and ∼2513 F g -1 by galvanostatic charge-discharge at a current density of 0.5 A g -1 in 6M KOH electrolyte. This may be owing to elegant redox activity of Ce 3+ /Ce 4+ ions and high conductivity of CQDs. The capacitance retention was found ∼97 % after 2000 GCD cycles.